Recognition of cyclic‐di‐GMP by a riboswitch conducts translational repression through masking the ribosome‐binding site distant from the aptamer domain. (25th April 2018) - Inuzuka, Saki; Kakizawa, Hitoshi; Nishimura, Kei‐ichiro; Naito, Takuto; Miyazaki, Katsushi; Furuta, Hiroyuki; Matsumura, Shigeyoshi; Ikawa, Yoshiya
Abstract : The riboswitch is a class of RNA‐based gene regulatory machinery that is dependent on recognition of its target ligand by RNA tertiary structures. Ligand recognition is achieved by the aptamer domain, and ligand‐dependent structural changes of the expression platform then usually mediate termination of transcription or translational initiation. Ligand‐dependent structural changes of the aptamer domain and expression platform have been reported for several riboswitches with short (<40 nucleotides) expression platforms. In this study, we characterized structural changes of the Vc2 c‐di‐GMP riboswitch that represses translation of downstream open reading frames in a ligand‐dependent manner. The Vc2 riboswitch has a long (97 nucleotides) expression platform, but its structure and function are largely unknown. Through mutational analysis and chemical probing, we identified its secondary structures that are possibly responsible for switch‐OFF and switch‐ON states of translational initiation. Abstract : The Vc2 c‐di‐GMP riboswitch has a long (97 nucleotides) expression platform. Through mutational analysis and chemical probing, we identified its secondary structures that are possibly responsible for switch‐OFF and switch‐ON states of translational initiation.